Potential of Urochloa grass hybrids as fodder in the Ethiopian highlands - Worku, Mesfin; Lemma, Habtamu; Shawle, Kassa; Adie, Aberra; Duncan, Alan J.; Jones, Christopher S.; Mekonnen, Kindu; Notenbaert, An Maria Omer; Bezabih, Melkamu (Wiley, 2022)
Urochloa grasses have shownpromising results for smallholders to cope with feed shortages in tropical Africa. The objective of this study was to evaluate the performance of two Urochloa hybrids, Mulato‐I and Mulato‐II, in the Ethiopian highlands when managed under different plant spacing and harvesting stages. Treatments included three plant spacings for root splits (0.5 by 0.25 m, 0.5 by 0.5 m, and 0.75 by 0.75 m between rows and plants, respectively) and three harvesting stages: (a) 60 d of growth; (b) 90 d of growth corresponding to 50% bloom, and (c) 120 d of growth (corresponding to full bloom). Experimental plots were laid out in a randomized complete block design with three replications, and observations on the same established stands were made in two consecutive years. Varietal differences were observed in plant height (Mulato‐II: 42 cm; Mulato‐I: 72 cm), and herbage accumulation (Mulato‐II: 3.0 Mg dry matter [DM] ha–1; Mulato‐I: 10.6 Mg DM ha–1). Plant spacing also affected the above variables, but year of harvest influenced herbage accumulation. The rate of herbage accumulation tended to be constant, while that of crude protein (CP) declined and fiber concentration increased significantly with advancing maturity. Overall, the decline in quality at full bloom stage appears to be compensated by the greater herbage accumulation, suggesting that farmers can have enough time window to harvest the forages. While Mulato‐I was superior in herbage accumulation, Mulato‐II was found to be better in forage quality. The two grasses have potential to supply good quality forage provided proper management practices are applied.